Primulina linearicalyx (Gesneriaceae), a new species from Guangxi, China - Wen, Fang; Lai, Bi-Dan; Zhao, Zhi-Guo; Wang, Bing-Mou; Wei, Yi-Gang (Phytotaxa, 2016)
Primulina linearicalyx from Wuming County, Guangxi, is illustrated and described here. It is morphologically close to P. linearifolia, P. pseudolinearifolia and P. longgangensis, but it can be easily distinguished by the exceptionally long and linear-lanceolate to linear calyx lobes. The chromosome number for this species, being reported the first time, was determined to be 2n=36. The conservation status of the new species was assessed as “Critically Endangered” (CR) based on IUCN criteria.